Eksplorasi Literasi Sains untuk Anak Usia Dini - Rizki Febriandani; Yetti, Elindra; Utami, Ade Dwi (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
Science literacy in early childhood is an essential competency that must be cultivated from an early age to address the challenges of the 21st century. This article aims to answer key questions regarding the concept of science literacy in early childhood. The study employs a Literature Review method, analyzing 30 relevant scholarly articles published within the last decade. The findings indicate that science literacy in early childhood encompasses the ability to understand basic scientific concepts, think critically, and apply this knowledge in daily life. Effective strategies for developing science literacy include storytelling with fiction and non-fiction books, simple experiments, observation, and the use of interactive media supported by technology. Furthermore, science literacy is influenced by several supporting factors, such as the active role of teachers, the integration of technology in learning, and a conducive learning environment for exploration. This article concludes that fostering optimal science literacy in early childhood not only enhances scientific thinking skills but also prepares children to navigate the advancements in science and technology in the future.